2018
DOI: 10.3390/su11010133
|View full text |Cite
|
Sign up to set email alerts
|

How does Perceived Destination Social Responsibility Impact Revisit Intentions: The Mediating Roles of Destination Preference and Relationship Quality

Abstract: This study applied the relationship quality theory to examine how destination social responsibility (DSR) impacts revisit intentions through the mediation of destination preference and relationship quality (i.e., tourist satisfaction and identification). An integrated model was proposed and tested by using survey data from an urban tourism attraction in China. The findings indicate that DSR positively impacts destination preference and tourist satisfaction, but it does not have a significant influence on touri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 96 publications
3
21
0
2
Order By: Relevance
“…This finding is consistent with previous studies (e.g. Tong & Wong, 2014 ; Su, Swanson, & Chen, 2015 ; Su & Huang, 2019 , Su, Gong et al, 2020 , Su, Hsu et al, 2020 , Su, Lian, et al, 2020 ) demonstrating that DSR has a significant impact on visitors’ intention to repeat visitation. These results also supported the study of Su, Gong et al (2020) , Su, Hsu et al (2020) , Su, Lian, et al (2020) , which revealed that the impact of DSR motive attributions on trust vary under different conditions of DR.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with previous studies (e.g. Tong & Wong, 2014 ; Su, Swanson, & Chen, 2015 ; Su & Huang, 2019 , Su, Gong et al, 2020 , Su, Hsu et al, 2020 , Su, Lian, et al, 2020 ) demonstrating that DSR has a significant impact on visitors’ intention to repeat visitation. These results also supported the study of Su, Gong et al (2020) , Su, Hsu et al (2020) , Su, Lian, et al (2020) , which revealed that the impact of DSR motive attributions on trust vary under different conditions of DR.…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the stakeholder theory, firms leverage CSR activities to exert an impact on various stakeholders, including tourists, employees, and community residents [30]. The extant tourism CSR research has started to consider CSR actions primarily as connections to shareholders' values [22,29], customers' behavior [31,32], employee-associated outcomes [25,26], and residents' attitudes and support [11,16]. Therefore, the following hypothesized relationship is proposed: Hypothesis 1 (H1).…”
Section: Destination Social Responsibility and Pro-tourism Behaviorsmentioning
confidence: 99%
“…On the other side, the destination’s environmental degradation is considered to be influential factor in explaining tourists’ intention not to return (Alegre and Garau, 2010). Su and Huang (2019) and Su et al (2020a, b) empirically showed that a destination’s social responsibility orientation can make tourists feel satisfied and adopt more positive behaviors toward the destination. For instance, Su and Huang (2019) concluded that destinations that are engaging in practices related to destination social responsibility (DSR), such as minimizing the tourism carbon footprint, adopting responsible environmental standards in tourism attractions, offering certifications for sustainable destinations, etc., provide better tourism experiences, which is reflected in tourist satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%